Evaluating the long-term care insurance policy from medical expenses and health security equity perspective: evidence from China - Huan Liu; Tiantian Hu (BMC, 2022)
Abstract Background Since the national long-term care (LTCI) policy pilot in 2016 of China, the LTCI policy has had significant impact on the residents in the pilot area. Methods From the perspective of medical expenses and health security equity, this study selects tracking survey data from the CHARLS database in 2013, 2015, and 2018 and empirically investigates the effect of LTCI policy pilot by using differences-in-differences method (DID). Moreover, this study measures the economic distribution and health equity of the treated and untreated groups using the concentration and Theil indices. Results The results showed that group heterogeneity of medical expenses and health level of elderly in the treatment group were narrowing. Moreover, the policy results showed that the LTCI policy pilot significantly affects the outpatient, hospital expenses, and length of stay of elders. Residence registration, income level, and basic medical insurance play a significant regulatory role. Additionally, LTCI policy pilot significantly improved the overall health of the elderly. Conclusions The measurement results of inequality show that the policy increases the income of low-income people, lowers the inequality level of outpatient and inpatient reimbursement, and reduces the concentration index of ADL disability and serious diseases. However, the inequality of serious diseases is becoming higher. Based on this, this paper provides several suggestions on optimizing the pilot policy of LTCI.